Struggle for Love of Albert Brennaman in Andy Tennant's Hitch Movie (2005): An Individual Psychological Approach, - VIRGIAWAN L, ACEF S (2012)
The problem of this study is to reveal how the struggle for love in major character. The objectives of the study is to analyze the major character in Hitch movie based on Individual Psychological Approach. The study is a literary study, which can be categorized into a descriptive qualitative study. The object of this study is Hitch movie. The data sources are primary and secondary data sources. The primary data source is the movie Hitch script and the secondary data sources are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive analysis. The structural elements of the movie bring us to take a close view at how the movie embodies and shows all the events. It can be divided into eleven; namely, characters and characterization, setting, plot, point of view, theme, casting, mise_en_scene, cinematography, sound and editing. Based on the analysis, the writer concludes that the problem faced by the major character is struggle to get his love, the writer use individual psychological perspective such as: Inferiority Feeling, Striving for Superiority, Fictional Finalism, Style of Life, Social Interest, and Creative Power. Based on An Individual Psychological aspects shown in the film, the writer then concludes that literary work reflects the condition of person who has a dream or goal and his struggle to get it